The role of miR-409-3p in regulation of HPV16/18-E6 mRNA in human cervical high-grade squamous intraepithelial lesions - Sommerova, Lucia; Anton, Milan; Bouchalova, Pavla; Jasickova, Hedvika; Rak, Vladimir; Jandakova, Eva; Selingerova, Iveta; Bartosik, Martin; Vojtesek, Borivoj; Hrstka, Roman (Antiviral research, 2019)
Cervical cancer is one of the most common malignancies in women. MicroRNAs (miRNAs) are involved in a variety of fundamental cellular processes, including carcinogenesis. The potential utilization of aberrantly expressed miRNAs as novel biomarkers in cervical cancer diagnostics is growing. We investigated miRNA expression profiles during the progression of dysplasia in cervical epithelium to identify aberrantly expressed miRNAs. High-throughput miRNA profiling of high-grade precancerous lesions identified 79 miRNAs showing significant difference in expression values compared to normal cervical epithelium. Ten selected miRNAs were subsequently measured in an independent group of samples to validate them as promising biomarkers of cervical carcinogenesis. MicroRNAs miR-10b-5p, miR-34c-5p, miR-409-3p and miR-411-5p were confirmed as downregulated, while miR-10a-5p, miR-132-3p, miR-141-5p were significantly upregulated in dysplastic cervical tissues. Further investigation revealed an inverse correlation of miR-409-3p with E6 mRNA levels in precancerous cervical lesions. Subsequent in vitro analyses showed a direct involvement of this miRNA in the regulation of E6 oncogene levels, thus confirming a potential tumor suppressor function of miR-409-3p in cervical malignancies. Hence, miR-409-3p may represent a useful early marker and a potential therapeutic target for cervical cancer.
Keywords: down regulace; Gene Expression Regulation, Neoplastic; represorové proteiny; MicroRNAs; Squamous Intraepithelial Lesions; Up-Regulation; Cell Line, Tumor; Human papillomavirus 18; onkogenní proteiny virové; Uterine Cervical Neoplasms; nádory děložního čípku; mikro RNA; regulace genové exprese u nádorů; LSIL; upregulace; E6 mRNA; lidský papilomavirus 18; stanovení celkové genové exprese; Human papillomavirus 16; HSIL; Gene Expression Profiling; lidský papilomavirus 16; Down-Regulation; lidé; ženské pohlaví; Humans; Cervical cancer; hsa-miR-409-3p; Repressor Proteins; HPV; miRNA; nádorové buněčné linie; Female; skvamózní intraepiteliální léze; Oncogene Proteins, Viral